Energy absorption of shape memory structures - Koh, Justin Yue Siang (2013)
This project was conducted to observe the ability of a Nickel-Titanium (Nitinol) Shape Memory Alloy to absorb energy. The samples are in the shape of a circular thin wall tube and qausistatic lateral cyclic compression tests were carried out in a series of loading and unloading test. Force exerted on the specimen was slowly increased per cycle till failure occurred. The specimen was also tested in various honeycomb structures to determine its energy absorption properties as a unit. From the Force Vs Displacement loops plotted, energy absorbed can be obtained from the area inside these loops. The resultant energy values amounted were compared which shows that specimens placed in the honeycomb square arrangement displayed the best energy absorbing properties. Apart from qausistatic testing, the specimen was compressed at various speeds to compare any relationship between energy absorption property and speed of loading. The results showed little reduction in energy absorbing properties at higher speeds. Finally, dynamic testing by the means of a Split-Hopkinson Pressure Bar Test was conducted. The author was unable to achieve a Stress vs Strain Curve for the dynamic test due to the lack of a transmission pulse.